Strategi Pengembangan Agribisnis Bawang Merah Di Desa Genengadal Kecamatan Toroh Kabupaten Grobogan - Nanda, Fitra Nanda Dewi; Winarsih (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2024)
Background :Central Java is the highest shallot producing province and Grobogan Regency, Central Java Province is one of the areas where the majority of the population makes a living as farmers and is one of the shallot production areas. This shallot production area is often found in Genengadal Village in Toroh District. Almost all residents plant shallots when the planting season arrives, making it a superior product and there is great hope of earning a decent income from the cultivation of shallots. Marketing that confronts farmers in Genengadal Village is related to problems with the shallot system. Shallot marketing is the activity of delivering shallot commodities from farmers to consumers with the aim of obtaining monetary value as compensation for the results of the commodity. So the strategy for developing shallot commodities is important because apart from the limited amount of research, it is also to find strategies on how to encourage the competitiveness of local onion commodities to seize local market opportunities in order to improve farmers' welfare. Methods :This research aims to determine what internal, external factors and development strategies are carried out by shallot farmers in Genengadal Village, Toroh District, Grobogan Regency. This research is qualitative research involving 5 farmer sources from Genengadal Village, Toroh District, Grobogan Regency. Data analysis uses observation, interviews, questionnaires, documentation. Results :The research results show that the opportunity for market demand is increasing, promising selling prices and machine support from the government are external factors that influence production, then farmer experience, cultivation techniques, land area and capital are internal factors that influence shallot production in Genangadal Village. Conclusion : The most influential factor is that if there is an increase in market prices then land expansion becomes the main factor for sources in meeting market needs.